Hepatic COX1 loss leads to impaired autophagic flux and exacerbates nonalcoholic steatohepatitis - Qian Yu; Chang Li; Qinghui Niu; Jigang Wang; Zhaodi Che; Ke Lei; He Ren; Boyi Ma; Yixing Ren; Pingping Luo; Zhuming Fan; Huan Zhang; et al. (Elsevier, 2023)
The mechanisms underlying autophagic defects in nonalcoholic steatohepatitis (NASH) remain largely unknown. We aimed to elucidate the roles of hepatic cyclooxygenase 1 (COX1) in autophagy and the pathogenesis of diet-induced steatohepatitis in mice. Human nonalcoholic fatty liver disease (NAFLD) liver samples were used to examine the protein expression of COX1 and the level of autophagy. Cox1Δhepa mice and their wildtype littermates were generated and fed with 3 different NASH models. We found that hepatic COX1 expression was increased in patients with NASH and diet-induced NASH mice models accompanied by impaired autophagy. COX1 was required for basal autophagy in hepatocytes and liver specific COX1 deletion exacerbated steatohepatitis by inhibiting autophagy. Mechanistically, COX1 directly interacted with WD repeat domain, phosphoinositide interacting 2 (WIPI2), which was crucial for autophagosome maturation. Adeno-associated virus (AAV)-mediated rescue of WIPI2 reversed the impaired autophagic flux and improved NASH phenotypes in Cox1Δhepa mice, indicating that COX1 deletion-mediated steatohepatitis was partially dependent on WIPI2-mediated autophagy. In conclusion, we demonstrated a novel role of COX1 in hepatic autophagy that protected against NASH by interacting with WIPI2. Targeting the COX1-WIPI2 axis may be a novel therapeutic strategy for NASH.